2016
DOI: 10.1063/1.4941601
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope phase dependence of the directional fragmentation and hydrogen migration in toluene in few-cycle laser fields

Abstract: The dissociative ionization of toluene initiated by a few-cycle laser pulse as a function of the carrier envelope phase (CEP) is investigated using single-shot velocity map imaging. Several ionic fragments, CH3+, H2+, and H3+, originating from multiply charged toluene ions present a CEP-dependent directional emission. The formation of H2+ and H3+ involves breaking C-H bonds and forming new bonds between the hydrogen atoms within the transient structure of the multiply charged precursor. We observe appreciable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…However, quantum interference may not be the dominant mechanism of the selective bond breaking of CO 2 because many excited states could be involved in the dissociation process. 39 Indeed, unlike D 2 + , 27 the asymmetry parameter shows no clear dependence on the total kinetic energy E kin in the field intensity range investigated in the present study (not shown, see Fig. 4…”
Section: Methodsmentioning
confidence: 49%
“…However, quantum interference may not be the dominant mechanism of the selective bond breaking of CO 2 because many excited states could be involved in the dissociation process. 39 Indeed, unlike D 2 + , 27 the asymmetry parameter shows no clear dependence on the total kinetic energy E kin in the field intensity range investigated in the present study (not shown, see Fig. 4…”
Section: Methodsmentioning
confidence: 49%
“…Moreover, it has been demonstrated that controlling the CEP permits selective breaking of either C-H bond, leading to directional proton emission [32,33]. Very recently, we have reported on the control of the preferential direction of hydrogen migration in acetylene and allene [34], and toluene [35] using the CEP of a few-cycle laser pulse. Here, we go beyond studies at a single intensity of the laser field and report on combined CEP and intensity studies of the strong-field-induced dissociative ionization of acetylene and allene.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35]). CEP effects in the deprotonation of acetylene, induced by few-cycle laser pulses, have attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling molecular structure rearrangements using ultrashort laser fields has attracted enormous interest for the last decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Chemical transformations can be controlled with various laser parameters, including intensity, pulse duration, chirp, and the electric field waveform.…”
Section: Introductionmentioning
confidence: 99%
“…The control of reactions occurring in hydrocarbon molecules is interesting from both a fundamental and an application point of view. The processes that may be steered with tailored fields include C-H and C-C bond breaking and proton migration reactions [4,6,[13][14][15][16]. A prototype system is acetylene, where it was demonstrated that both the directionality of the deprotonation [6,14] and proton migration [13] can be steered with the CEP of few-cycle pulses in the visible to near-infrared (NIR) region.…”
Section: Introductionmentioning
confidence: 99%